KONSEKUENSI PERNIKAHAN SIRI TERHADAP ISTRI DAN ANAK - Fajarwati (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
Islam regulates family matters not in outline, but in detail. This shows a great concern for the welfare of the family. The family is formed through marriage, therefore marriage is highly recommended by Islam for those who already have the ability. The purpose of marriage according to Islam is to fulfill religious instructions in order to establish a harmonious, prosperous and happy family. Harmonious in using the rights and obligations of family members; Prosperous means the creation of inner and outer peace due to the fulfillment of the necessities of life both physically and mentally, so that happiness arises, namely love between family members. If you look at the purpose of marriage above, then sirri marriages that occur in society will be difficult to establish a harmonious, prosperous and happy family. Because sirri marriage contains more harm than benefit. One of the disadvantages is that the wife and children will not get inheritance from the husband. Thus, this sirri marriage is very detrimental to the woman. Therefore, carry out the marriage in accordance with the rules in Islamic law and the Marriage Law.